(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the policy of the Soviet government in Turkestan on the vakuf property during the early years of the foundation of the Soviet power. Based on the analysis of archival documents and other sources, the author scientifically substantiated the religious policy of the Soviet government in Turkestan